2009
DOI: 10.1371/journal.ppat.1000340
|View full text |Cite
|
Sign up to set email alerts
|

Definition of Herpes Simplex Virus Type 1 Helper Activities for Adeno-Associated Virus Early Replication Events

Abstract: The human parvovirus Adeno-Associated Virus (AAV) type 2 can only replicate in cells co-infected with a helper virus, such as Adenovirus or Herpes Simplex Virus type 1 (HSV-1); whereas, in the absence of a helper virus, it establishes a latent infection. Previous studies demonstrated that the ternary HSV-1 helicase/primase (HP) complex (UL5/8/52) and the single-stranded DNA-Binding Protein (ICP8) were sufficient to induce AAV-2 replication in transfected cells. We independently showed that, in the context of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
69
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 45 publications
0
69
0
2
Order By: Relevance
“…Activation of the p5 promoter by ICP0 also involves the interaction of ICP0 with the deubiquitylating enzyme USP7/HAUSP, which, however, is not essential [135,137]. It was recently shown that transactivation of rep expression by ICP0 can be further enhanced by the presence of two other HSV-1 IE proteins, ICP4 and ICP22 [138]. On their own, ICP4 stimulates rep expression only marginally, while ICP22 has no effect [138].…”
Section: Hsv-1-based Gene Therapy Vectorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Activation of the p5 promoter by ICP0 also involves the interaction of ICP0 with the deubiquitylating enzyme USP7/HAUSP, which, however, is not essential [135,137]. It was recently shown that transactivation of rep expression by ICP0 can be further enhanced by the presence of two other HSV-1 IE proteins, ICP4 and ICP22 [138]. On their own, ICP4 stimulates rep expression only marginally, while ICP22 has no effect [138].…”
Section: Hsv-1-based Gene Therapy Vectorsmentioning
confidence: 99%
“…It was recently shown that transactivation of rep expression by ICP0 can be further enhanced by the presence of two other HSV-1 IE proteins, ICP4 and ICP22 [138]. On their own, ICP4 stimulates rep expression only marginally, while ICP22 has no effect [138]. ICP4 is a transactivator protein essential for HSV-1 replication and is required for expression of several early and late genes [139].…”
Section: Hsv-1-based Gene Therapy Vectorsmentioning
confidence: 99%
See 3 more Smart Citations